Nutritional characteristics and value-added products of Chickpea (Cicer arietinum) - a review - Kaur, Ravneet; Prasad, Kamlesh (Journal of Postharvest Technology, 2021)
Chickpea is an important leguminous crop in terms of both production and consumption. It has been widely consumed since centuries for its protein-rich  seeds. It enriches the staple diet and provides balanced protein when consumed along with cereals. This review is mainly focused on the nutritional  composition of chickpea and its application in the food systems. Chickpea consists of about 18-22% protein content and is a sustainable source of  protein, mainly for the vegetarian population. Chickpea has been utilized in the preparation of various traditional food products as the base ingredient or  as an admixture. Chickpea in the form of ‘dhal’ and ‘besan’ accounts for maximum consumption. Besan is used to form dough or batter for the preparation  of various food products like boondi, soft chapatti or chilla, pokaras, bhujia and sweets. Besides this, it is used in the preparation of several value-added  products like bakery products, snacks, extruded products, weaning foods, roasted chickpea, roasted chickpea flour, and plant-based beverages.  Consumption of chickpea is associated with several health benefits like anti-diabetic, anti-inflammatory, hypo-cholesterolemic and prevention of  cardiovascular diseases.
Keywords: Bengal gram; chickpea; cicer arietinum; value added product; nutritional composition